Perancangan Sistem Informasi Pendaftaran dan Pengelolaan Ekstrakulikuler di SMK Swasta Nahdlatul Ulama 2 Medan Menggunakan Metode Waterfall - Kurniawan Kurniawan; Furqan Khalidy; Satriandi Satriandi (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
The management of extracurricular activities at SMK Swasta Nahdlatul Ulama 2 Medan is still conducted manually, making the registration process, data management, and report generation less effective and more prone to administrative errors. This study aims to design and develop a web-based information system for extracurricular registration and management to improve the effectiveness and efficiency of administrative processes. The research employed an applied research approach using software engineering principles with the Waterfall development model, consisting of requirements analysis, system design, implementation, testing, and maintenance. Data were collected through observations and structured interviews with the Vice Principal for Student Affairs and extracurricular supervisors. The results indicate that the developed system simplifies the registration process and supports integrated management of student, supervisor, and extracurricular activity data. Furthermore, the system provides faster, more accurate, and easily accessible information, facilitating administrative tasks, data retrieval, report generation, and activity monitoring. Therefore, the web-based information system developed using the Waterfall method effectively improves the quality and efficiency of extracurricular activity management at the school.